HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN TOLAK PELURU SISWA SMA NEGERI 15 PEKANBARU - Heza Hartoyo; Ramadi Ramadi; NI Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find out whether the explosive power of the legs has a significant correlation with the bullet repulsion ability in Pekanbaru 15 High School students. Samples selected using atechnique purposive sample, so that 60 samples were obtained. Research data on leg limb explosions were obtained from vertical jump movements performed by the sample. While data on the ability of the shot is obtained from the bullet treatment. Data analysis and research hypothesis testing using correlation analysis techniques productmoment with a level significan of α = 0.05, From the data analysis can be obtained results that; (1) there is no correlation between leg muscle power (X) with the o'brient style bullet repulsion ability (Y) in male students of Pekanbaru 15 High School r count = 0.039 < r table = 0.254. This means that the hypothesis is rejected. Conclusion The hypothesis was accepted at a significant level = 0.05 in other words there was no significant relationship between leg muscle power and o'brien-style shot put result abilities in male students of Pekanbaru 15 High School.Key Words: Correlation, Power limb muscles, shot put